ANTI HOAX CAMPAIGN: RESEARCH BASED - Levina Tania; Gracia Marindra; Melissa Melissa; Violetta Alviyani; Ivanna Risty; Risalina Risalina (MANASA, 2017)
Increasing number of hoax and hate speech which has destructive consequences for the community is a concern. This study aims to explore the attitude toward hoax of Jakarta society. Data were collected using survey involves 204 participants. The results indicate that participants already had a good knowledge of hoax. They showed negative feelings to the hoax information. However, even though majority of participants were already aware with the negative consequences as a result of the spread of hoax information, most of them were still passive in responsing the hoax information. Based on the results, a campaign were designed which take location in the area of car free day Jakarta on May 14th, 2017. The purpose of this campaign is to promote awareness of hoax and its damaged consequences, and persuade audiences to take a role in minimizing the spread of hoax information using social media. The campaign has been published in a number of leading newspapers in Indonesia.